2020
DOI: 10.1002/adma.201906590
|View full text |Cite
|
Sign up to set email alerts
|

Direct Imprinting of Quasi‐3D Nanophotonic Structures into Colloidal Quantum‐Dot Devices

Abstract: Three‐dimensional (3D) subwavelength nanostructures have emerged and triggered tremendous excitement because of their advantages over the two‐dimensional (2D) counterparts in fields of plasmonics, photonic crystals, and metamaterials. However, the fabrication and integration of 3D nanophotonic structures with colloidal quantum dots (CQDs) faces several technological obstacles, as conventional lithographic and etching techniques may affect the surface chemistry of colloidal nanomaterials. Here, the direct fabri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 45 publications
0
35
0
Order By: Relevance
“…Recently, Tang et al reported a HgTe QD-based dual-diode MIR photodetector with two-channel-polarization sensing ability. [81] The authors first de- [79] Copyright 2015, Springer Nature. c) The false color SEM image of the filterless narrow-band infrared detectors consisting of transfer-patterned HgSe QD film, interdigitated electrodes, and the patterned plasmonic disk arrays.…”
Section: Spectral-or Polarization-selective Photodetectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Tang et al reported a HgTe QD-based dual-diode MIR photodetector with two-channel-polarization sensing ability. [81] The authors first de- [79] Copyright 2015, Springer Nature. c) The false color SEM image of the filterless narrow-band infrared detectors consisting of transfer-patterned HgSe QD film, interdigitated electrodes, and the patterned plasmonic disk arrays.…”
Section: Spectral-or Polarization-selective Photodetectionmentioning
confidence: 99%
“…reported a HgTe QD‐based dual‐diode MIR photodetector with two‐channel‐polarization sensing ability. [ 81 ] The authors first developed a pressure‐mediated nanoimprint technique that was capable of placing a quasi‐3D metallic nanostructure (such as grating, polarizer, and metal mesh) at a given depth of the HgTe QD active layer to achieve absorption enhancement or polarization‐ or wavelength‐selection. Figure 7e shows one example device—a two‐channel polarization detector in which a bilayer wire‐grid polarizer was embedded in the QD layer.…”
Section: Photonic Structure‐enhanced Qd‐based Light‐absorbing Devicesmentioning
confidence: 99%
“…The key is to develop a fast and reliable parallel inkjet printing method. Besides 2D CQDs patterning techniques, Tang et al reported a direct imprinting technique for producing high resolution CQDs quasi-3D optical nanostructures without degrading the key properties of materials [71]. The direct imprinting technique process was shown in Figure 5c.…”
Section: Multispectral Cqds Photodetectorsmentioning
confidence: 99%
“…It is worth noting that the development of actuators also brings great promise for the development of next-generation smart products such as wearable devices and electronic skins. [24,25] Moreover, the rapid development of stimuli-responsive materials, [26] new structural design, [27] micro-nano processing technologies (including photolithography, [28] laser process, [29] incusing [30] and layer-bylayer self-assembly [31] ) and new actuation technologies (including electrostatic [8] or piezoelectric actuation, [32] magnetic remote control, [33] optical tweezers [34] and pneumatic systems [35] ) pro-vides favorable conditions for the design and manufacture of actuators. [36] Among the numerous external stimuli, humidity has been paid more and more attention, and the research on humidityresponsive actuators is gaining popularity among researchers.…”
Section: Introductionmentioning
confidence: 99%